Quality yield measure for processes with asymmetric tolerances - Pearn, WL; Lin, PC; Chang, YC; Wu, CW (My University, 2006)
Process capability indices provide numerical measures on whether or not a process is able to produce products that meet prespecified quality targets and are often used by manufacturers to evaluate manufacturing performance. Although process yield is the primary focus of the performance criteria, a formula that combines the yield and the average process loss, called the quality yield index, has been developed. This index, the quality yield, can be viewed as the conventional process yield minus the truncated expected relative process loss within the specifications. Although cases with symmetric tolerances dominate in practical situations, cases with asymmetric tolerances can also occur. In this paper, we generalize the quality yield index for asymmetric tolerances. The generalization technique is justified, and some statistical properties of the estimated generalization are investigated. An application example on high-density light emitting diodes is also presented to illustrate the applicability of the generalization.